Situation wirtschaftlich wichtiger Grundfischbestände vor Norwegen, Spitzbergen und in der Barents-See - Schöne, Rüdiger (1996)
Assessments on NE-arctic stocks of cod, haddock, saith, redfish and Greenland halibut were carried out by the ICES 'Arctic Fisheries Working Group' in August 1996. Whereas stocks of cod, haddock, and saithe are presently in fairly good and stable condition the assessments show the stocks of beaked redfish and Greenland hailibut to be just the opposite. The status of the golden redfish stock seems to be stable. More detailed information is given in this report.